Amino sulfonic acids, peptidosulfonamides and other related compounds. Issue 13 (29th March 2018) - Grygorenko, Oleksandr O.; Biitseva, Angelina V.; Zhersh, Serhii
Abstract: A review with 636 references. The literature on saturated amino sulfonic acids with primary/secondary amino group and their derivatives from XIX century to 2016 is surveyed, focusing mainly on results published in the last two decades. Synthesis of saturated amino sulfonic acids and their derivatives, their occurrence among natural products, as well as their use for design of peptidomimetics, conjugates with various molecules of practical significance, applications as building blocks for drug discovery and for other reasons are discussed. Graphical abstract: